Flood-Irrigated Corn - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn production.
MF578_1995_10
Keywords: MF578; Economics; Crops; MF